Human immunodeficiency virus testing uptake and risk behaviours in Spain. Issue 7 (13th March 2009) - de la Fuente, L; Suarez, M; Belza, M J; Vallejo, F; García, M; Álvarez, R; Castilla, J; Rodés, A; ,
Abstract : Background: The purpose of this study was to estimate the prevalence of human immunodeficiency (HIV) testing in the general population; to analyse factors related to voluntary testing; and to describe the main reasons for testing, the kinds of health services where testing takes place and the relations between self-risk perception and HIV testing. Methods: A probability sample survey of health and sexual behaviour in men and women aged 18–49 years and resident in Spain in 2003 (n = 10 980) was used. A combination of face-to-face and computer-assisted self-interview was used, and bivariate and multivariate logistic regression analyses were performed. Results: Some 39.4% (40.2% in men and 38.5% in women) had ever been tested, blood donation being the main reason for men and pregnancy for women. In the multivariate analysis, HIV testing was associated with foreign nationality, high educational level, having injected drugs and having a large number of sexual partners. In men, it was also associated with age 30–39 years, having had sex with other men and having paid for sex. About 29.3% of men and 32.8% of women had their last voluntary HIV test in primary healthcare centres, whereas only 3.4% of men and 3.6% of women had last been tested in sexually transmitted infection/HIV diagnostic centres. About 20.2% of men and 5.5% of women with risk behaviours had never been tested. Conclusion: The proportion of men with risk behaviours who have never had an HIV test is unacceptably high in Spain. Scaling up access to HIV testing in this population group remains a challenge for health policies and research.